2002
DOI: 10.1097/00024382-200209000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Role of NFAT and AP-1 in PGE2-Mediated T Cell Suppression in Burn Injury

Abstract: PGE2 is known to suppress T cell proliferation and IL-2 production in many inflammatory conditions. Previous studies from our laboratory have shown that such suppression of T cell proliferation in burn and sepsis could result from alteration in T cell activation signaling molecule p59fyn. In this study, we examined the role of downstream signaling molecules NFAT and AP-1 in PGE2-mediated suppression of T cell in burn injury. These studies were carried out utilizing splenic T cells from sham and burn rats 3 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
13
1
1
Order By: Relevance
“…While IL-10 is a known immunomodulatory cytokine that keeps the immune system in homeostasis, it is also induced by prostaglandin E2 (PGE2). Furthermore, PGE2 can affect the immune system without the help of IL-10 by blocking T-cell IL-2 autocrine activity 14-17 .…”
Section: Discussionmentioning
confidence: 99%
“…While IL-10 is a known immunomodulatory cytokine that keeps the immune system in homeostasis, it is also induced by prostaglandin E2 (PGE2). Furthermore, PGE2 can affect the immune system without the help of IL-10 by blocking T-cell IL-2 autocrine activity 14-17 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that severe burn (~25% TBSA) alone results in alterations in T cell receptor associated src kinases P59 fyn and other downstream signaling molecules PKC activity, and Ca 2+ signaling (40; 135; 155–161). Additional findings suggest that while a relatively small burn injury (~12.5% TBSA) does not produce alterations in T cells signaling, when combined with prior alcohol exposure it produces changes in T cell signaling similar to those observed after severe burn.…”
Section: Potential Signaling Mechanisms Of T Cell Differentiationmentioning
confidence: 99%
“…Similarly, JNK is a complex of 46-and 54-kDa proteins. The role of intracellular signaling molecules has been investigated in altered T cell functions after burn injury, trauma, and sepsis (Hoyt et al 1991;Faist et al 1996;Choudhry et al 1995Choudhry et al , 1998Choudhry et al , 1999bChoudhry et al , c, 2001bChoudhry et al , 2002bChoudhry et al , 2004a. Although findings from some of these studies support the role of src family kinases, P56lck and P59fyn, in decreased T cell proliferation (Choudhry et al 1995(Choudhry et al , 1998(Choudhry et al , 1999b(Choudhry et al , c, 2001b(Choudhry et al , 2002b(Choudhry et al , 2004a, results from other studies have suggested that alterations in PKC and Ca 2+ signaling are likely the cause for T cell dysfunction after burn, trauma, and sepsis (Hoyt et al 1991;Faist et al 1996).…”
Section: Corticosterone and Alterations In T Cell Intracellular Signamentioning
confidence: 99%
“…The role of intracellular signaling molecules has been investigated in altered T cell functions after burn injury, trauma, and sepsis (Hoyt et al 1991;Faist et al 1996;Choudhry et al 1995Choudhry et al , 1998Choudhry et al , 1999bChoudhry et al , c, 2001bChoudhry et al , 2002bChoudhry et al , 2004a. Although findings from some of these studies support the role of src family kinases, P56lck and P59fyn, in decreased T cell proliferation (Choudhry et al 1995(Choudhry et al , 1998(Choudhry et al , 1999b(Choudhry et al , c, 2001b(Choudhry et al , 2002b(Choudhry et al , 2004a, results from other studies have suggested that alterations in PKC and Ca 2+ signaling are likely the cause for T cell dysfunction after burn, trauma, and sepsis (Hoyt et al 1991;Faist et al 1996). Additional results obtained from these studies indicate that alterations in the signaling component could result from a shift in the cytokine milieu in the vicinity of T cells, such as elevated levels of IL-10, transforming growth factor-beta (TGF-β), and prostaglandin E 2 (PGE2) (Hoyt et al 1991;Faist et al 1996;Choudhry et al 1995Choudhry et al , 1998Choudhry et al , 1999aChoudhry et al , 2001aChoudhry et al , 2002bSchwacha and Chaudry 2002;Schwacha et al 2003;Murphy et al 2004;Angele and Chaudry 2005;Cabral 2005).…”
Section: Corticosterone and Alterations In T Cell Intracellular Signamentioning
confidence: 99%